CHEMICAL CHARACTERIZATION AND RADICAL SCAVENGING ACTIVITY OF AMOMUM AGASTYAMALAYANUM V. P. THOMAS AND M. SABU (ZINGIBERACEAE) - SINITHA K; RENJANA PK; JOHN ERNEST THOPPIL (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The objective of the study is to analyze the chemical composition of the methanolic extract of Amomum agastyamalayanum, an endemic species to the Western Ghats of South India, and to evaluate its antioxidant potential. Methods: The chemical constituents were analyzed by gas chromatography/mass spectrometry (GC/MS) and high-resolution liquid chromatography (HR-LC)/MS. Quantitative estimation of major phytocomponents, including phenolics, terpenoids, and flavonoids, was done. Antioxidant activity was assessed using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, superoxide radical scavenging, lipid peroxidation inhibition, and ferric reducing antioxidant power (FRAP) assays. Results: GC/MS and HR-LC/MS analyses revealed the presence of several bioactive components. The extract was found to be rich in terpenes such as 5β-cholestan-3-one ethylene acetal, 1-hexacosene, β-guaiene, caryophyllene, aromadendrene, α-cedrene oxide, and rosifoliol. The methanolic extract showed high phytochemical content, with phenolics (88.41±3.06 mg gallic acid equivalents [GAE]/g dry weight [DW]), terpenoids (106.67±3.83 mg linalool/g DW), and flavonoids (94.05±6.37 mg QE/g DW) as the major constituents. The extract exhibited strong antioxidant activity, with IC50 values of 47.26±1.00 μg/mL for DPPH, 40.66±3.53 μg/mL for superoxide radical scavenging, and 27.72±2.37 μg/mL for lipid peroxidation inhibition. FRAP was significant, showing a reducing capacity equivalent to 7.12±0.48 μmoL/mL FeSO4·7H2O at 10 μg/mL. Conclusion: The methanolic extract of A. agastyamalayanum is rich in bioactive phytochemicals and exhibits potent antioxidant activity, highlighting its potential as a natural source of antioxidant compounds for pharmaceutical and nutraceutical applications.